The Contribution of the Brain–Gut Axis to the Human Reward System - Katerina Karaivazoglou; Ioanna Aggeletopoulou; Christos Triantos (Biomedicines, 2024)
The human reward network consists of interconnected brain regions that process stimuli associated with satisfaction and modulate pleasure-seeking behaviors. Impairments in reward processing have been implicated in several medical and psychiatric conditions, and there is a growing interest in disentangling the underlying pathophysiological mechanisms. The brain–gut axis plays a regulatory role in several higher-order neurophysiological pathways, including reward processing. In this context, the aim of the current review was to critically appraise research findings on the contribution of the brain–gut axis to the human reward system. Enteric neuropeptides, which are implicated in the regulation of hunger and satiety, such as ghrelin, PYY3–36, and glucagon-like peptide 1 (GLP-1), have been associated with the processing of food-related, alcohol-related, and other non-food-related rewards, maintaining a delicate balance between the body’s homeostatic and hedonic needs. Furthermore, intestinal microbiota and their metabolites have been linked to differences in the architecture and activation of brain reward areas in obese patients and patients with attention deficit and hyperactivity disorder. Likewise, bariatric surgery reduces hedonic eating by altering the composition of gut microbiota. Although existing findings need further corroboration, they provide valuable information on the pathophysiology of reward-processing impairments and delineate a novel framework for potential therapeutic interventions.